2016
DOI: 10.1007/s11999-015-4260-7
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn From 20-year Followup Studies of Hip Replacement?

Abstract: Background A patient who dies during the followup period of a study about total hip arthroplasty (THA) cannot subsequently undergo a revision. The presence of competing events (such as deaths, in a study on implant durability) violates an assumption of the commonly used Kaplan-Meier (KM) survivorship approach. In that setting, KM-based estimates of revision frequencies will be high relative to alternative approaches that account for competing events such as cumulative incidence methods. However, the degree to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
12
0
2
Order By: Relevance
“…The relative difference between KM and CI estimations was increasing during follow-up, reaching up to 76.8% at 25 years. Thus, similarly to other reports, we found that the KM analysis overestimated significantly the risk of revision in comparison to the CI method (28-31). If this observation has an important clinical significance, remains to be examined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The relative difference between KM and CI estimations was increasing during follow-up, reaching up to 76.8% at 25 years. Thus, similarly to other reports, we found that the KM analysis overestimated significantly the risk of revision in comparison to the CI method (28-31). If this observation has an important clinical significance, remains to be examined.…”
Section: Discussionsupporting
confidence: 91%
“…It was then suggested that the CI approach provides more accurate results, especially in studies with long-term follow-up, including high number of deaths. This method provides more profound analysis into THR outcomes, allowing comparisons of survival results between different studies (29)(30)(31). These studies followed by a CORR's Editorial, by Wongworawat et al, suggesting the use of an alternative to KM analysis, when the frequency of competing event is greater than 10%-20% and the follow-up duration reach out 10 years (21).…”
Section: Discussionmentioning
confidence: 99%
“…The wear of the prosthetic implants is an important problem in the field of orthopedics. Several research works have shown adverse effects caused by nanoparticles release induced by the wear of implants inside the patients' body (Charnley, 2012;Learmonth, Young, & Rorabeck, 2007;Martin et al, 2016). The cobaltchromium-molybdenum (CoCrMo) alloy is used in artificial hip and knee prosthesis due to its hardness and good corrosion resistance as well as its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…В связи с постоянно увеличивающимся количеством операций у относительно молодых пациентов с большой предполагаемой продолжительностью жизни и, как правило, высоким уровнем двигательной активности, нарастает риск ревизий, выполняемых в значительно меньшие сроки [16,17,19]. границы молодого возраста для эндопротезирования ТБс, по данным разных авторов, колеблются от 50 до 65 лет, но подавляющее число исследований все же принимает в расчет именно 50 лет [5,17,[19][20][21][22][23][24]. Молодые пациенты обладают гораздо более высоким уровнем активности после операции, что ведет к ускоренному разрушению трущихся поверхностей, и многочисленные исследования демонстрируют взаимосвязь скорости изнашивания с развитием остеолиза, асептического расшатывания и частотой ревизий.…”
Section: Introductionunclassified
“…Молодые пациенты обладают гораздо более высоким уровнем активности после операции, что ведет к ускоренному разрушению трущихся поверхностей, и многочисленные исследования демонстрируют взаимосвязь скорости изнашивания с развитием остеолиза, асептического расшатывания и частотой ревизий. соответственно, показатели выживаемости имплантатов при тотальном эндопротезировании тазобедренного сустава у пациентов молодого возраста существенно хуже, чем в других возрастных группах [17,19,21,24,25].…”
Section: Introductionunclassified